Contrastive Analysis of Discourse-pragmatic Aspects of Linguistic Genres - Aijmer, Karin; Lewis, Diana (Springer International Publishing : Imprint: Springer, 2017)
This volume will give readers insight into how genres are characterised by the patterns of frequency and distribution of linguistic features across a number of European languages. The material presented in this book will also stimulate further corpus-based contrastive research including more languages, more genres and different types of corpora. This is the first thematic volume of the Yearbook of Corpus Linguistics and Pragmatics, a publication that addresses the interface between the two disciplines and offers a platform to scholars who combine both methodologies to present rigorous and interdisciplinary findings about language in real use. Corpus linguistics and Pragmatics have traditionally represented two paths of scientific thought, parallel but often mutually exclusive and excluding. Corpus Linguistics can offer a meticulous methodology based on mathematics and statistics, while Pragmatics is characterized by its effort in the interpretation of intended meaning in real language.
Keywords: Linguistics.; Comparative literature.; Application software.; Sociolinguistics.; elektronické knihy; electronic books